PENGARUH PENDIDIKAN, EKONOMI DAN BUDAYA ORANG TUA TERHADAP PERNIKAHAN USIA MUDA DI KECAMATAN KARIMUN JAWA KABUPATEN JEPARA TAHUN 2015 - Hantrini, Nanik Marati (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2016)
This study aims to determine the effect of the of education, economic and cultural for early marriage.Sampling was carried out with saturated sampling technique. The sample in this study were elderly womenwho marry at an early age. data collection methods with methods of documentation and questionnaires /questionnaire is used to obtain data on the education variable, variable economic , cultural variables andvariable wedding early.Teknik data analysis used is descriptive percentages and regression analysis. Theresults showed no effect of level of education, economic and cultural conditions to the effectiveness of earlymarriage regression line 65.11% and the effective contribution of 23.8% variable X1, X2 11.2%, 30.1%Variable X3. At the significant level of 5% by dk = (1: n-2) = (1: 103) was obtained Ftabel Amounting3.0532572. Because F_hitung> Ftabel and significant value <0.05 then Ho is accepted.